Early Result of TEVAR for Thoracic Aortic Aneurysm: An Experience in Ramathibodi Hospital - Nath Rojanakit (2022)
Background: Traditional treatment of patients with thoracic aortic aneurysms is open surgical graft replacement. At present, thoracic endovascular aortic repair (TEVAR) is an alternative option for treat patients who have high surgical risk. The authors retrospectively reviewed result of TEVAR in patients diagnosed with thoracic aortic aneurysm in Ramathibodi Hospital in 5 years, especially mortality, postoperative morbidity. Objective: To evaluate a results of TEVAR for thoracic aortic aneurysm and to identify post-operative complication. Material and Methods: The authors reviewed data from patients who were diagnosed with thoracic aortic aneurysm and underwent TEVAR procedure at Ramathibodi Hospital from 1 January 2014 to 31 December 2018. Baseline characteristics and post procedural imaging were collected and analyzed. Univariate analysis was used to identify risks associated with endoleak. Survival and reintervention rate were estimated using Kaplan-Meier methodology and between groups comparison was analyzed using the log rank test. Results: Total 33 patients were included in the analysis, with a mean age of 68.57 years. There were 7 patients with endo leak (21.21%). Endo leak was more common in male (6 out of 7, 85.70%). Renal failure occurred in only 1 patient from all (3.00%). Stroke and/or paraplegia was found in 1 patient (3%) and respiratory complication in 5 patients (15.10%). Two patients in non endoleak group died (6.1% of all). No incidence of graft migration and distal sine (stent induced new entry tear). Operative time was found to be associated with risk for developing endo leak (p-value=0.015, 95% CI 1.00 to 1.03). Conclusion: TEVAR procedure for thoracic aortic aneurysm in Ramathibodi Hospital has low in mortality and postoperative complications. However, longer operative time is associated with an increased risk in endoleak in TEVAR procedure.